FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - WIRA ANDI KURNIAWAN; TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to examine the factors that influence dividend policy. These factors are liquidity, profitability, debt policy, firm size, company growth, institutional ownership, free cash flow, and investment opportunity set. Population of this research are non financial companies listed on Indonesian Stock Exchange from 2010 until 2015. The samples are collected using purposive sampling method and there are 74 companies meet those criteria for samples. This research use multiple regression method for data analysis. The result of this research indicate that liquidity, profitability, firm size, company growth, and institutional ownership have influence to dividend policy. While debt policy, free cash flow, and investment opportunity set do not have influence to dividend policy.Keywords: Divi